IMPLEMENTATION OF ISLAMIC VALUE-BASED CHARACTER EDUCATION THROUGH ISLAMIC CURRICULUM INTEGRATION AT MUHAMMADIYAH II KRAMAT ELEMENTARY SCHOOL, CENTRAL JAKARTA - Rosita, Ita (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
The increasing demand for effective and innovative instructional strategies has encouraged educators to adopt learner-centered approaches that promote active participation and engagement in the learning process. This study aims to examine the effectiveness of an implemented learning strategy in enhancing student engagement, motivation, and perceived learning effectiveness within an educational context. A quantitative research design was employed to analyze the relationship between the instructional strategy and students’ learning experiences. Data were collected through a structured questionnaire distributed to students participating in the learning activities. The collected data were analyzed using descriptive statistics, correlation analysis, and regression analysis to examine the relationships among the variables. The study's results indicate that implementing the learning strategy positively influences student engagement and perceived learning effectiveness. Descriptive analysis revealed that the majority of participants expressed positive perceptions regarding the strategy, suggesting that the instructional approach was generally well-received by students. Furthermore, the correlation analysis demonstrated a significant positive relationship between the implementation of the strategy and student engagement. Regression analysis also confirmed that the instructional approach significantly predicts improvements in learning outcomes. These findings highlight the importance of implementing innovative, learner-centered teaching strategies to create more interactive and effective learning environments. The study contributes to the growing body of literature emphasizing the role of instructional design in improving students’ learning experiences. Future research is recommended to explore additional variables, such as technological integration and self-regulated learning, to provide a more comprehensive understanding of the factors influencing learning effectiveness.